Antidiabetic Activity Of Nypa Fruticans WURMB. Vinegar - Md Yusoff, Nor Adlin (2017)
Nypa fruticans Wurmb. vinegar, locally known as nipa palm vinegar (NPV) in Malaysia, is believed to have remarkable antidiabetic properties. This study sought to elucidate the vinegar’s antidiabetic activity and possible mechanisms of action. Liquid– liquid extraction was used to separate the compounds in NPV based on polarity into an ethyl acetate extract (EE) and an aqueous extract (AE). AE was further fractionated using acid hydrolysis into two sub-fractions: SFI and SFII. NPV, EE, AE, SFI and SFII were administered using oral gavage in non diabetic and/or diabetic rats induced by streptozotocin (STZ). Blood glucose levels (BGLs), insulin levels, and liver and pancreatic histological changes were recorded.